Peran Persepsi Dalam Memediasi Pengaruh Marketing Mix pada Niat Beli Wisatawan di Bali Zoo - Respati, Ni Nyoman Rsi; Aksari, Ni Made Asti (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This study aims to determine the role of perception in mediating the effect of marketing mix on purchase intention. It is important for business people whom engaged in the tourism industry to offering the right product. This research is located at Bali Zoo Gianyar,Bali. The population were foreign and domestic tourists who visited Bali Zoo. From the sampling process, 200 respondents completed the questionnaire completely. The sampling technique used was random sampling method. This study uses path analysis techniques to find the direct and indirect effects of independent variables on the dependent variable. To obtain data and measure research indicators using a questionnaire instrument and measured by a Likert scale. The result of this study shows that perception plays an important role in influencing purchase intention. Marketing mix and perception become factors influences purchase intention. This needs to be taken into account by the management of Bali Zoo. Keywords : Marketing Mix; Perception; Purchase Intention.